Matemática financeira no ensino médio : uma proposta metodológica de ensino - Oliveira, Bruno Henrique de (2015)
In this research work, we address concepts related to Financial Mathematics. In this way, we have developed a methodology of teaching which is different than traditional method. In addition to the traditional content of this school stage (Percentage; Accruals and discounts, simple interest or compound) also approached contents that are usually presented only in courses aimed at forming a professional who has knowledge of finance in the fields of Business Administration, Economics, Accounting, etc. . These contents were financing with fixed installments, amortization and application systems with regular deposits. In our methodology we value teamwork, problem solving, research and working with tools that are available to any individual, such as the calculator (scientific), the "Calculadora do cidadão", an application available by the Central Bank and the www.calculador.com.br site.